2020
DOI: 10.1371/journal.pone.0230933
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and caregiver burden in chronic pain patients: A cross-sectional clinical study

Abstract: Insomnia is a major comorbid symptom of chronic pain and is likely to affect caregiver burden. This cross-sectional study investigated the association between insomnia in chronic pain patients and family caregiver burden. Participants were 60 patients with chronic pain of �3 months duration. Demographic and clinical information were collected using the Athens Insomnia Scale (AIS), the Pain Disability Assessment Scale (PDAS), the Hospital Anxiety and Depression Scale (HADS), and a pain intensity numerical ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
(37 reference statements)
0
12
1
Order By: Relevance
“…However, our study did show that patients' depression and disability were correlated with caregiver burden, a result similar to that of the previous study. [11] Cognitive-behavioral therapy has been shown to improve the self-efficacy and chronic pain of patients. [34] Therefore, it is an important treatment for these patients that can also influence caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study did show that patients' depression and disability were correlated with caregiver burden, a result similar to that of the previous study. [11] Cognitive-behavioral therapy has been shown to improve the self-efficacy and chronic pain of patients. [34] Therefore, it is an important treatment for these patients that can also influence caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…While caregiver support of chronic pain patients is important because of patients’ decreased activities of daily living, [ 10 ] caregivers who provide substantial daily support often face considerable physical and mental burdens. Although a previous study revealed that depression, insomnia, and disability were related to the caregiver burden for such patients, [ 11 ] evidence regarding relationships between caregiver burden, patient self-efficacy, and the factors of pain chronicity in chronic pain patients is still lacking. We hypothesized that in chronic pain patients, factors of pain chronicity and low self-efficacy would be associated with increased caregiver burden through an increased need for support of daily activity.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain has negative effects on ability to perform activities of daily living and may increase the burden on caregivers [ 31 ]. As the number of older people with chronic pain increases, so will the social burden.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with weather-related disease, several batteries have been applied for clinical research. They include i) pain assessment: Numerical Rating Scale (NRS), ii) functional behavior assessment: Pain Disability Assessment Scale (PDAS) [10], iii) psychosocial assessment: Hospital Anxiety and Depression Scale (HADS) [11], iv) assessment for pain in detail: Pain Self-Efficacy Questionnaire (PSEQ) [12,13], and Pain Catastrophizing Scale (PCS) [14].…”
Section: Abbreviationsmentioning
confidence: 99%